Enhancing Students’ Skill in Writing an Argument through Brainwriting: A CAR at second grade of Gunung Kaler 2 Junior High School in Tangerang Regency - Dini Fitriani; Yadi Kusmayadi; Megawati Megawati; Fadilla Oktaviana (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
The target of class is second grade students of Gunung Kaler 2 Junior High school in Tangerang Regency, the subjects of this study were conducted toward students of class VII A which contains of 32 students in the class. The purpose of this study was to enhance students' writing skill in argument throughbrainwriting. It is a qualitative research that using a classroom action research method. In this research consist 3 cycles, where each cycle consists of 4 steps namely planning, acting, observation, and reflecting. The data collected through observation, writing test, and interview. The result of the research showed that students’ writing skill in argument could enhance significantly after applied brainwriting to them. For KKM score is 75, it could seemed from the percentage in cycle one was 61. Then in cycle two percentage became 86, the percentage became 100% Based on the data collected that implementing braiinwriting could enhance students’ writing skill in argument. Because through brainwriting makes students could be understand deeply related text types accordance of the context use and students could create the text well. Based on the explanation above, it could be conclude that enhancing students’ writing in argumenttive through brainwriting was effective way in teaching learning process especially in learning writing in argument.